2022
DOI: 10.18502/ijpa.v17i3.10619
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Blastocystis Subtypes in Children with Functional Abdominal Pain and Celiac Disease in Çorum, Turkey

Abstract: Background: Blastocystis has been associated with various symptoms of the gastrointestinal tract. We aimed to investigate the prevalence of Blastocystis in children with celiac disease (CeD) or functional abdominal pain (FAP) and to evaluate its subtypes (STs) with respect to demographic, socioeconomic and epidemiological factors. Methods: Overall, 161 fecal samples were collected from healthy children and patients with FAP or CeD in Hitit University Erol Olçok Research and Training Hospital, Corum, Turk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Blastocystis hominis is protozoa commonly found in the gastrointestinal tract of humans and a wide variety of animals can be acquired via the fecal-oral route through contaminated water and food or can be by exposure to animals. (Güreser et al, 2022). In this study, we found that opportunistic intestinal protozoan infection was more commonly isolated from boys than girls, this is probably because boys are more active in playing outside the orphanage and are less concerned about their hygiene.…”
Section: Resultsmentioning
confidence: 56%
“…Blastocystis hominis is protozoa commonly found in the gastrointestinal tract of humans and a wide variety of animals can be acquired via the fecal-oral route through contaminated water and food or can be by exposure to animals. (Güreser et al, 2022). In this study, we found that opportunistic intestinal protozoan infection was more commonly isolated from boys than girls, this is probably because boys are more active in playing outside the orphanage and are less concerned about their hygiene.…”
Section: Resultsmentioning
confidence: 56%
“…In a study evaluating Blastocystis subtypes in children with functional abdominal pain and celiac disease in Türkiye, there was no difference in Blastocystis prevalence between study groups. ST2, ST3, and ST1 were the most common subtypes, respectively (Güreser et al 2022). In a study that determined the prevalence and subtypes distribution of Blastocystis among school-aged children in Thailand, the most common subtypes were ST3, followed by ST1 and ST2 (Abu et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The infection is associated with at least 14 STs (ST1‐ST10, ST12, ST14, ST16, and ST24) in humans and animals, suggesting a high likelihood of zoonotic transmission. Additionally, more than 95% of Blastocystis cases in humans are thought to be caused by ST1–ST4 (Güreser et al., 2022; Maloney et al., 2022). Some STs are highly host‐specific, for example, ST5 commonly infects pigs while ST6 and ST7 predominate in birds.…”
Section: Introductionmentioning
confidence: 99%